1998
DOI: 10.1080/07315724.1998.10718787
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and Zinc Status of Head and Neck Cancer Patients: An Interpretive Review

Abstract: In this review, we provide evidence based on our studies, for zinc deficiency and cell mediated immune disorders, and the effects of protein and zinc status on clinical morbidities in patients with head and neck cancer. We investigated subjects with newly diagnosed squamous cell carcinoma of the oral cavity, oropharynx, larynx, and hypopharynx. Patients with metastatic disease and with severe co-morbidity were excluded. Nutritional assessment included dietary history, body composition, and prognostic nutrition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0
4

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 26 publications
4
52
0
4
Order By: Relevance
“…Dietary Zn deficiency has been linked to many human cancers, including esophageal SCC 10, head and neck 11, and digestive tract cancers 12. Likewise, studies of rodent models of chemically induced esophageal and forestomach cancers have shown that Zn deficiency results in significantly more tumors and more severe histopathological lesions 13, 14.…”
Section: Introductionmentioning
confidence: 99%
“…Dietary Zn deficiency has been linked to many human cancers, including esophageal SCC 10, head and neck 11, and digestive tract cancers 12. Likewise, studies of rodent models of chemically induced esophageal and forestomach cancers have shown that Zn deficiency results in significantly more tumors and more severe histopathological lesions 13, 14.…”
Section: Introductionmentioning
confidence: 99%
“…Jaiswal and Narayan [43] reported that zinc inhibits the proliferation of colon cancer cells. In head and neck cancers, systemic zinc deficiency was associated with increased tumor size and stage of the cancer [44]. Zinc (and copper) is significantly lower in human hepatoma tissue compared with those in the surrounding "normal" hepatic tissue; and the plasma zinc level is significantly lower in hepatoma subjects compared with the subjects without known liver disease [45].…”
Section: Tumor Suppressor Effects Of Zinc In Other Tumor Cellsmentioning
confidence: 99%
“…Thus, deficits in zinc intake could have a significant impact on the development of cancer. Epidemiological studies have shown decreased zinc status in cancer patients compared with healthy controls (9)(10)(11)(12). It has also been suggested as a contributor to esophageal cancer in humans (9,13).…”
mentioning
confidence: 99%